FITOTREATMENT SEBAGAI POLISHING TREATMENT AIR LIMBAH SEKTOR PERIKANAN DI PASAR TRADISIONAL DENGAN MENGGUNAKAN SALVINIA MOLESTA DAN PISTIA STRATIOTES - Ardiansyah Putra, Muhammad Zidane; Tangahu, Bieby Voijant (Department of Environmental Engineering-Faculty of Civil, Planning, and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2022)
Fisheries activities produce wastewater with high levels of BOD, COD, and TSS that are dangerous if discharged directly into the river. One of the treatments that can be done is by using phytotreatment or processing using plants. The plants used in this study are Salvinia molesta and Pistia stratiotes. The stages of this research are propagation, acclimatization, range finding test, and phytotreatment test stage. The fisheries sector wastewater used in this study came from UPT Pasar Gresik with a pH of 6.54, BOD 310 mg/L, COD 853.3 mg/L, TSS 590 mg/L and UPT Pasar Giri wastewater with a pH of 6.48, BOD 292 mg/L, COD 746.6 mg/L, TSS 440 mg/L. Based on the RFT test, Pistia stratiotes is able to survive at a concentration of 20% for Gresik Market wastewater and 40% for Giri Market wastewater while Salvinia molesta can survive at a concentration of 10% for Gresik Market wastewater and 10% for Giri Market wastewater. From the phytotreatment test, the results obtained for the removal of BOD, COD, and TSS parameters in Giri Market wastewater, Pistia stratiotes plants are more effective in reducing BOD levels by 84.6% and COD 80.6% while for TSS levels Salvinia molesta plants are more effective with a removal of 89.8%. Then for the removal of BOD, COD, and TSS parameters in Gresik Market wastewater, Pistia stratiotes plants are more effective in reducing BOD levels by 92.4% and COD 84.4% while for TSS levels Salvinia molesta plants are more effective with a removal of 90.9%.